The Influence of Economic Growth on Regional Original Revenue in Jayapura City, 2014–2023 - Muh. Iqbal; Agustina Ester Antoh; Rachmaeny Indahyani; Transna Putra Urip S; Anita Rusianti; Maria Kbarek (Journal of International Conference Proceedings, 2025)
Economic growth plays an important role in strengthening local fiscal capacity, particularly through Regional Original Revenue, which reflects the financial independence of local governments. This study analyzes the effect of economic growth on Regional Original Revenue in Jayapura City during the period 2014–2023 using a quantitative approach. The research applied classical assumption tests, including normality, autocorrelation, and heteroscedasticity, followed by simple linear regression, hypothesis testing, and coefficient of determination analysis. The results indicate that the model meets all statistical assumptions, ensuring its validity for interpretation. The analysis reveals a positive and significant relationship between economic growth and Regional Original Revenue, supported by a t-test significance of 0.001, which is less than the 0.05 criterion. The coefficient of determination (R²) is 0.752, showing that 75.2% of the variation in Regional Original Revenue is explained by economic growth, while 24.8% is influenced by other factors. The study concludes that sustained economic growth is crucial for strengthening fiscal independence in Jayapura City.